2004
DOI: 10.1002/chin.200404154
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Activity of Novel Glutathione Analogues Containing an Urethane Backbone Linkage.

Abstract: Backbone Linkage. -The new glutathione analogues (I), characterized by the replacement of central cysteine with either serine or aspartic acid and containing a urethanic fragment as isosteric substitution of the scissile γ-glutamylic junction, are synthesized in good overall yields using solution procedures by stepwise elongation of the peptide chain in the C-to-N direction. The results of the biological studies are discussed. -(CACCIATORE, I.; CACCURI, A. M.; DI STEFANO, A.; LUISI, G.; NALLI, M.; PINNEN*, F.;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…H-Cys(Allyl)-OBu t (6). A suspension of H-Cys-(Allyl)−OH (4.16 g, 25.8 mmol) in AcOBu t (375 mL) was slowly added to HClO 4 (7.74 mL) at 20 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…H-Cys(Allyl)-OBu t (6). A suspension of H-Cys-(Allyl)−OH (4.16 g, 25.8 mmol) in AcOBu t (375 mL) was slowly added to HClO 4 (7.74 mL) at 20 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…A variety of GSH derivatives have been extensively studied to discover therapeutic molecules for the treatment of the above-reported disorders. Unfortunately, GSH possesses some limitations in its pharmacological use due to its unfavorable pharmacokinetic properties, having a plasmatic half-life lower than 3 min . These disadvantages can be overcome using the prodrug strategy, a medicinal-chemistry-based approach widely used to enhance the delivery features of drugs .…”
Section: Introductionmentioning
confidence: 99%
“…Its analogues, individual compounds, , and several prodrug molecules have been proposed as GST-inhibiting strategies. Furthermore, several GSH analogues have been proposed as more specific reversible and irreversible GST inhibitors, exploiting the high affinity of GSTs for the tripeptide substrate GSH. An alternative concept exploits the susceptibility of GSH conjugates (products of GST catalysis) against the GSH-degrading enzyme γ-glutamyltranspeptidase (γGT).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is a general hallmark of major neurodegenerative disorders, leading to neuronal cell dysfunction and progressive death [ 270 ]. Glutathione (GSH), lipoic acid (LA), carnosine, and caffeic acid provide potent antioxidant assistance in counteracting the free radicals produced by the ROS [ 222 , 271 ]. One study revealed that SLNs encapsulating LA can be used for the topical delivery of LA as an antiaging agent [ 272 ], with enhanced stability and hydrophilicity [ 273 ].…”
Section: Applications Of Slns In Cns Disordersmentioning
confidence: 99%